Analisis Kinerja Keuangan PT Bank Rakyat Indonesia (Persero) Tbk Menggunakan Rasio Keuangan Periode Tahun 2020-2024 - Zahwa Zahrotul Fitriyah; Ajeng Tita Nawangsari (AKUNTANSI 45, 2026)
This study aims to analyze the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk during the 2020-2024 period using five key banking ratios: Return on Assets (ROA), Return on Equity (ROE), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM). This study uses a quantitative descriptive approach based on secondary data obtained from BRI’s annual reports and consolidated financial statements. The results show that BRI has successfully maintained stable and positive financial performance growth throughout the study period. The increase in ROA and ROE reflects increasingly strong profitability, supported by operational efficiency and optimization of productive assets. A CAR that is consistently well above Bank Indonesia’s minimum requirements indicates a healthy capital structure. Meanwhile, a stable LDR ratio indicates the bank’s ability to channel credit effectively without disrupting liquidity. The upward trend in NIM demonstrates BRI’s success in managing interest income and reducing funding costs. Overall, the analysis shows that digital transformation through the BRIvolution 2.0 program and the establishment of the Ultra Micro Holding Company have significantly contributed to increasing BRI’s profitability, efficiency, and competitiveness in the national banking industry.